2002
DOI: 10.1523/jneurosci.22-02-00389.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Uptake through the Norepinephrine Transporter in Brain Regions with Low Levels of the Dopamine Transporter: Evidence from Knock-Out Mouse Lines

Abstract: Selective blockers of the norepinephrine transporter (NET) inhibit dopamine uptake in the prefrontal cortex. This suggests that dopamine in this region is normally cleared by the somewhat promiscuous NET. We have tested this hypothesis by comparing the effects of inhibitors selective for the three monoamine transporters with those of a nonspecific inhibitor, cocaine, on uptake of 3H-dopamine into synaptosomes from frontal cortex, caudate nucleus, and nucleus accumbens from wild-type, NET, and dopamine transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
381
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(418 citation statements)
references
References 46 publications
27
381
2
Order By: Relevance
“…Our current observations that cocaine does not increase DA ex in NAc of homozygous DAT-KO mice contrasts with the nearly-intact cocaine reward found in these animals (Rocha et al, 1998;Sora et al, 1998). These in vivo microdialysis data are also consistent with studies which document failure of cocaine to block DA uptake in NAc samples taken from DAT homozygous mice in in vitro experiments (Budygin et al, 2002;Moron et al, 2002). The current data also fail to provide simple correlations with models that postulate that enhanced PFc DA levels are necessary and sufficient for cocaine reward.…”
Section: Differential Da Responses In To Cocaine In Cpu Nac and Pfcsupporting
confidence: 87%
See 1 more Smart Citation
“…Our current observations that cocaine does not increase DA ex in NAc of homozygous DAT-KO mice contrasts with the nearly-intact cocaine reward found in these animals (Rocha et al, 1998;Sora et al, 1998). These in vivo microdialysis data are also consistent with studies which document failure of cocaine to block DA uptake in NAc samples taken from DAT homozygous mice in in vitro experiments (Budygin et al, 2002;Moron et al, 2002). The current data also fail to provide simple correlations with models that postulate that enhanced PFc DA levels are necessary and sufficient for cocaine reward.…”
Section: Differential Da Responses In To Cocaine In Cpu Nac and Pfcsupporting
confidence: 87%
“…However, in vitro data fail to identify cocaine influences on CPu or NAc DA uptake in DAT-KO mice (Budygin et al, 2002;Moron et al, 2002). The simple idea that NET mediates cocaine reward in the absence of DAT is also incompatible with observations that cocaine reward is ablated in DAT/SERT double-KO mice that express normal levels of NET (Sora et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the V max for DA clearance in the mPFC was demonstrated in rats exposed to repeated foot-shock by voltammetry, but the data did not prove that this change in DA clearance was due to a change in DAT activity (Meiergerd et al 1997). In fact, several studies support the hypothesis that extracellular DA in this region is cleared primarily by the noradrenaline transporter (Di Chiara et al 1992;Carboni et al 1994;Tanda et al 1994;Yamamoto and Novotney 1998;Moron et al 2002) and a recent microdialysis study demonstrated that the DA measured in the PFC mainly represents the amine taken up and co-released from noradrenergic terminals (Devoto et al 2001). This finding raises the question of the functional significance of DA co-released with noradrenaline.…”
Section: Discussionmentioning
confidence: 91%
“…This finding raises the question of the functional significance of DA co-released with noradrenaline. Moreover, a cocaineinsensitive DA transporter has been observed in rat brain (Izenwasser and Cox 1990;Elsworth et al 1993) and suggested in mouse brain (Moron et al 2002). In the frontal cortex, the number of DAT binding sites has been measured, and the ratio of low-to high-affinity binding sites was found to be significantly higher there than in the CPu or NAc (Boja et al 1990;Boja et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is important because cocaine has comparable affinity for dopamine, norepinephrine (NET), and serotonin transporters, and cocaine's effects may be mediated in some regions via interactions with sites other than DAT. For example, frontal lobe dopamine uptake occurs primarily via NET activity (Moron et al, 2002). NET is present in cerebellum including vermis (Ding et al, 2003).…”
Section: Discussionmentioning
confidence: 99%